Desain Pengembangan Kurikulum Pendidikan Agama Islam Dalam Pendidikan Karakter Di Smp Negeri 13 Kaur - Dena Puja Puspita; Desy Eka Citra Dewi (JPT : Jurnal Pendidikan Tematik, 2024)
Curriculum development design is the arrangement or design of a curriculum model designed in accordance with the vision and mission of the school in its development through the process of validation, implementation and evaluation. This study is motivated by the practice of PAI in schools that are less than optimal, especially because of the lack of lesson hours. Seeing this problem, the development of PAI curriculum becomes very important to be done, both by related institutions and by PAI teachers themselves. The purpose of this study was to determine and analyze: the development of PAI objectives, the development of PAI substance, the development of PAI implementation, and the development of PAI evaluation. This research used a case study method using a qualitative approach. Data collection techniques were conducted by means of interviews, observations and documentation studies. Based on the results of the study, it was found that the development of PAI objectives is to develop academic abilities and prioritize Islamic character values in students. The development of PAI substance is developed into two forms, namely intracurricular form, in the form of Tarjamah subject and school culture form in the form of Tahfiz and Taqwa Character Building (TCB). The development of evaluation of PAI curriculum is carried out in two activities, namely evaluation by each school unit of SMP Negeri 13 Kaur.